Landscape of COVID-19 pandemic - Marín Sánchez, Obert (2020)
The World Health Organization received a report from the People’s Republic of China on atypical pneumonia in Wuhan City on December 31, 2019. Since the first report to date (April 30th), it has been 105 days, and little we know about the new coronavirus (SARS-CoV2) and COVID-19 disease. Epidemiological studies in recent years were already alerting about new coronavirus outbreaks, but were not taken into consideration, and this resulted in SARS-CoV2 being the first beta-coronavirus to reach pandemic status. Diagnosis is based on molecular evidence against the virus and serological tests for the disease. In addition, little is known about the mechanisms of contagion and transmission, and in turn the cellular and molecular mechanisms used by the virus for infection, and about immune response mechanisms are known. Finally, current efforts are focused on effective treatments and vaccine development; but now there are only vaccine candidates which are still in the clinical research phase and still require more time to be approved their use in the human population.